Testing for independence on statistically matched categorical variables. - De Veyra, Janna M. (University of the Philippines, 2018)
Abstract (In most instances, conducting a new survey is impossible due to time constraints and limited resources. Matching data sources has been used as a way to obtain a data set where all the intended variables. This paper propose the use of the MCMC and the inclusion of random error in matching categorical variables as well as the application of bootstrap procedure in testing for their independence. A simulation study indicates that the test is most effective when the proposed procedure are all applied because combining all these procedures produces a correctly sized test that yields the highest power among all other proposed procedures combined).